Analyzing urban population density gradient of Dhaka Metropolitan Area using Geographic Information Systems (GIS) and Census Data - Khatun, Hafiza; Falgunee, Nishat; Kutub, Md. Juel Rana (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Worldwide increase in urban population draws special attention to urban population density related research. Based on Thana level census data for the years 2001 and 2011, this study attempts to analyze the density gradient of urban population in Dhaka Metropolitan Area using Geographic Information Systems (GIS). Four mathematical functions have been considered to examine the change in population density with distance from CBD, after the classical work of Colin Clark in 1951. The density gradient appears to be following the negative exponential function. Result reveals that the density curve flattens over time, indicating greater increase of population density in the areas located further from the CBD than areas adjacent to it. GIS-based surface modeling using density contours shows the spatial pattern of population density has changed substantially. The study further corroborates that historical as well as economic factors are influencing the pattern and change of population density in Dhaka Metropolitan Area (DMA).